SYNTHESIS OF SILVER/COPPER NANOPARTICLES AND THEIR METAL-METAL BONDING PROPERTY - Kobayashi, Yoshio (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
The present paper describes a metal-metal bonding technique using Cu nanoparticles containing Ag nanoparticles (Ag/Cu nanoparticles).  The Ag/Cu nanoparticles with particle sizes of 30-85 nm and crystal sizes of 9.3 nm for Cu and 8.1 nm for Ag were produced by reducing 5.0×10-3 M Ag+ (AgClO4) and 5.0×10-3 M Cu2+ (Cu(NO3)2) simultaneously with 1.0 M hydrazine in aqueous solution containing 1.0 g/L poly(vinylpyrrolidone) as dispersing agent and 5×10-3 M citric acid as stabilizer at room temperature.  Discs of metallic Cu or metallic Ag were successfully bonded under annealing at 400oC and pressurizing at 1.2 MPa for 5 min in H2 gas with help of the Ag/Cu particles.  The shear strengths required for separating the bonded discs were as large as 19.7 for the Cu discs and 16.0 MPa for the Ag discs .